Origin and early diversification of phylum cnidaria: Key macrofossils from the ediacaran system of North and South America - Van Iten, Heyo (2016)
Recent molecular clock studies place the origin of phylum Cnidaria within the Cryogenian Period (ca. 850-635 Ma), with the split between the two subphyla (Anthozoaria and Medusozoa) likewise occurring during this time interval. However, the oldest cnidarian macrofossils, all medusozoans, occur in rocks of the late Ediacaran Period (ca. 560-541 Ma). Lightly skeletonized Corumbella werneri, currently known from late Ediacaran strata of Brazil, Paraguay and Nevada (USA), has been allied with coronate and conulariid scyphozoans, but it also shares gross morphological similarities with Carinachites spinatus, a possible conulariid from Cambrian Stage 1 (China), and it may be compared with Sinotubulites and Wutubus annularis from the late Ediacaran Dengying Formation (China). The strongest evidence of affinity with coronate scyphozoans is exhibited by Paraconularia sp. from a Corumbella -bearing shale interval in the latest Ediacaran Tamengo Formation of central Brazil. Furthermore, Paraconularia sp. from this rock unit establishes conulariids as a cnidarian clade that crossed the Proterozoic-Phanerozoic boundary. Finally, Haootia quadriformis from the late Ediacaran lower Fermeuse and Trepassy formations (southeastern Newfoundland, Canada) exhibits intriguing gross morphological similarities to extant staurozoans and may represent the earliest record of metazoan musculature. Together, C. werneri and latest Ediacaran Paraconularia sp. fix the split between the medusozoan classes Cubozoa and Scyphozoa at no later than ca. 543 Ma. If H. quadriformis was indeed a staurozoan or stem staurozoan, then this fossil taxon fixes the split between the class Staurozoa and all other medusozoan cnidarians at no later than ca. 560 Ma.